Child of the owl - Yep, Laurence, 1948- (New York : [Dell Publ. Co., Inc.], 1977)
A twelve-year-old girl who knows little about her Chinese heritage is sent to live with her grandmother in San Francisco's Chinatown.
Keywords: Chinese Americans -- California -- San Francisco -- Fiction; San Francisco (Calif.) -- Fiction; Grandmothers -- Fiction